Philippines : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper analyzes the factors behind the relatively strong performance of the Philippines in recent years (1990s) as well as the remaining reform agenda. The paper highlights that the Philippines has received considerable attention in recent years as it 'emerged' in the early 1990s from a long period of slow growth and economic imbalances, and then managed to escape the 'Asian crisis' relatively unscathed. The paper examines the public finances for the Philippines. It also analyzes the monetary sector, external sector, and the banking sector reforms.